Barbed versus conventional 2-layer continuous running sutures for laparoscopic vaginal cuff closure. Issue 39 (September 2016) - Kim, Jin Hwi; Byun, Seung Won; Song, Jae Yeon; Kim, Yeon Hee; Lee, Hee Joong; Park, Tae Chul; Lee, Keun Ho; Hur, Soo Young; Park, Jong Sup; Lee, Sung Jong
Abstract : Abstract: We compared results using unidirectional barbed sutures and conventional sutures for vaginal cuff closure during total laparoscopic hysterectomy (TLH).The electronic medical records and surgical videos of 170 patients who underwent TLH between January 2013 and March 2015 at Uijeong-bu St. Mary's Hospital of Catholic University of Korea were reviewed. Vaginal cuffs were closed using the 2-layer continuous running technique with unidirectional barbed sutures (V-Loc; Covidien, Mansfield, MA) in 64 patients and with polycolic acid Vicryl; Ethicon, Somerville, NJ sutures in 106 patients. Procedure time, clinical characteristics, and postoperative complications were compared between the 2 study groups. There were no differences in clinical characteristics (age, body mass index, and demographic data) between groups. The mean suturing time was significantly reduced in the barbed group (7.2 vs 12.2 minutes; P < 0.001), although the mean number of stitches was greater than in the Vicryl group (14.1 vs 12.3, P < 0.001). Perioperative complications, including episodes of vaginal bleeding, vaginal cuff cellulitis, and postoperative fever, did not differ between groups. There were no instances of vaginal cuff dehiscence in either group. Unidirectional barbed sutures can be used safely to reduce procedure time and surgical difficulty relative to conventional sutures in laparoscopic vaginal cuff closure.